2018
DOI: 10.3389/fpsyt.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to Parents As a Moderator in the Association between Sibling Bullying and Depression or Suicidal Ideation among Children and Adolescents

Abstract: Bullying is one of the most widespread phenomenon in childhood and adolescence. Interestingly, most research on bullying focuses on bullying at school and not on bullying among siblings at home. Sibling bullying is the most frequent form of repeated aggression that children experience in their lifetime. Furthermore, previous studies indicate that sibling bullying is associated with depression and self-harm behavior. However, the association between sibling bullying and suicidal ideation was never previously ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
3
24
2
2
Order By: Relevance
“…In addition, better peer relationship quality was associated with decreased odds that those in the high verbal victimization class would transition into the poly‐substance use or alcohol and cannabis only classes. This finding may reflect the buffering role of social support when experiencing stressful events (Davidson & Demaray, 2007), similar to studies of younger age groups showing, for example, that better parent–child relationship quality decreases the effects of bullying on health‐related outcomes (Bar‐Zomer & Brunstein Klomek, 2018). It may also be the case that for young adults with better peer relations, this derogatory language is coming from friends and thus perceived as more innocuous than if it were coming from nonfriends or strangers.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, better peer relationship quality was associated with decreased odds that those in the high verbal victimization class would transition into the poly‐substance use or alcohol and cannabis only classes. This finding may reflect the buffering role of social support when experiencing stressful events (Davidson & Demaray, 2007), similar to studies of younger age groups showing, for example, that better parent–child relationship quality decreases the effects of bullying on health‐related outcomes (Bar‐Zomer & Brunstein Klomek, 2018). It may also be the case that for young adults with better peer relations, this derogatory language is coming from friends and thus perceived as more innocuous than if it were coming from nonfriends or strangers.…”
Section: Discussionsupporting
confidence: 68%
“…This is perhaps the most sobering result of this study and it clearly outlines the risk for further bullying experiences when there is previous exposure at home. It highlights the importance of parenting and the family unit in the prevention of bullying involvement (Bar-Zomer & Brunstein Klomek, 2018;Lereya et al, 2013). Furthermore, it suggests that the effectiveness of anti-bullying programmes at the school level may have limited effectiveness if not considered within the wider community context.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been some international investigations of sibling bullying elsewhere (e.g., Tanrikulu & Campbell, 2015;Wolke & Samara, 2004), this is the first large-scale study to investigate this issue with adolescents in the Republic of Ireland. For the most part, current research has established a link between sibling bullying and mental health problems (particularly to depression; Bar-Zomer & Brunstein Klomek, 2018) and on the role of social support in preventing internalising problems (e.g., Coyle, Demaray, Malecki, Tennant & Klossing, 2017). As such, this study aims to build on previous international research on the implications of sibling bullying, while investigating this issue with an Irish population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Coyle et al (6) found that sibling bullying victimization was associated with increased risk for anxiety and depressive symptoms, over and beyond the experience of peer bullying in a sample of 372 US students. Similarly, Bar-Zomer and Klomek (15) reported an association between involvement in any kind of sibling bullying (victimization and perpetration) and greater risk for depression and suicidal ideation, using a sample of 279 Israeli students. In order to consolidate these findings, future replications are needed using prospective studies in large samples.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, research on the adverse outcomes of sibling bullying is still in its infancy. There is an emerging body of research linking sibling bullying in childhood to a range of internalizing and mental health problems both concurrently and prospectively (6, 1522).…”
Section: Introductionmentioning
confidence: 99%